ANALISIS MINYAK TERPENTIN (Pinus merkusii) HASIL PRODUKSI PERUSAHAAN LOKAL DAN PERDAGANGAN MENGGUNAKAN KROMATOGRAFI GAS-SPEKTROSKOPI MASSA (KG-SM) SERTA METODE PEMURNIANNYA - Amini, Rekfa Wika; Masruri, Masruri; Rahman, Mohamad Farid (Jurnal Ilmu Kimia Universitas Brawijaya, 2014)
A qualitative and quantitative analysis of the turpuntine oils was undertaken by means of gas chromatography and mass spectroscopy. Two types of sample was analyzed, one was bought from local market in Malang and a sample originally from local producer. Analysis was conducted directly from raw sample after drying over magnesium sulfate anhydrate and also after purification under fractional distillation. It was found that at least 13 compounds was detected contains of turpuntine oil sample from local producer and 10 compounds compose of sample from local market in Malang. α-Pinene as the main compound composes 64.63% from the first sample meanwhile sample from local market indicate in 55.75%. Moreover, fractional distillation under reduced pressure could provide α-pinene in 88.2% purity and 11.8% of δ-carene as the minor compound, respectively.   Keywords:  turpentine oil, α-pinene, GC-MS, essential oil